Forest Therapy in Germany, Japan, and China: Proposal, Development Status, and Future Prospects - Zhang, Zhiyong; Ye, Bing (Forests, 2022)
Forests have provided support for human health and survival since ancient times. With improved public awareness of health issues and the importance of forest ecological functions, forest therapy has gradually gained momentum. Forest therapies have been applied around the world as preventive and alternative therapies to promote human health. As a safe, side-effect-free, low-cost, preventive, and alternative therapy, forest therapy has been scientifically proven to promote physical and mental health in humans. However, the forest therapy service system is still underdeveloped, and forest therapy has not become a mainstream part of clinical medical treatment methods in most countries worldwide. Therefore, in order to better present the development path and current situation of forest therapy in different countries and provide guidance for how other countries can develop similar interventions and clinical sites to base these activities, this study uses Germany, Japan, and China as examples to systematically tease out how forest therapy has developed and the status of forest therapy services in different countries, as well as the health benefits of forest therapy. Furthermore, the key components and traditional cultural and socioeconomic backgrounds related to forest therapy are discussed. Finally, based on published empirical research, we believe that forest therapy can be a solution to public health problems thanks to its multiple, medically proven health benefits. Forest therapy facilitates the return of people to the forest and nature to achieve health and well-being effects. However, there is a need for more research on the mechanisms (such as the immune system, endocrine system, nervous system, etc.) underlying forest therapy’s effectiveness, which should include strengthened collaborations between disciplines. In addition, the role of forest therapy services in promoting human health needs to be emphasized.